(3LGFMI chQhfG (B:s (3LghO GdGMJhGA hGdOQhS GdeSJaGOI (B/s - (3YHO GdMcje, Cced,s 1966- ([(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3JQjfOR ddHMhK hGdGSJTGQGJ,s, 2022)
(3JCJj gPg GdhQbI Ydi NdajI eMGVQI CdbjJ Ydi HGMKj eQcR JQjfOR ddHMhK hGdGSJTGQGJ aj GdJGSY YTQ ef jfGjQ (B2022(3, JJHYJ ajgG GdfTCI GdJGQjNjI ddajQhSGJ YeheG, hajQhS zchajO(B-19(3yNUhUG, ceMGhdI deYQaI GdeTJQcGJ GdJj fTCJ eY cd ajQhS, heOi JTGHggG Ch GNJdGagG eY ajQhS zchajO(B-19(3y(B. (3hJSJYQV gPg GdhQbI GdLghO GdOhdjI GdJj HPdJ decGaMI zchajO(B-19(3y, ShGA JeKd Pdc aj LghO GdefXeGJ GdOhdjI Ch eHGOQGJ GdOhd GdJj bOeJgG, aj eMGhdI deMGUQI ajQhS chQhfG, hcja JVGaQJ Jdc GdLghO(B. (3ceG JJYQV GdhQbI deOi GdJeGjR GdPj CMOKJg Jdc GdeHGOQGJ aj ehGLgI Jdc GdLGFMI ef WQb ehGLgI GdajQhSGJ GdSGHbI hCSGdjHgG(B. (3ceG JJYQV cPdc dCge GdJMOjGJ GdJj hGLgJ GdHTQjI NdGd LghOgG dEjbGa GfJTGQ gPG GdajQhS, hGdJj bO JTcd JgOjOG cHjQG ddHTQjI, NGUI aj GdTb GdeJYdb HeG CUHM jYQa HhHGA GdCcGPjH GdeVddI GdJj CSgeJ aj Ndb HYV GdYQGbjd CeGe GdeLJeY GdOhdj, aj eMGhdJg eMGUQI gPG GdfhY ef GdLhGFM(B.s
Keywords: (3ajQhS chQhfG GdeSJLOs -- (3hbGjI hecGaMIs -- (3ebGdGJ heMGVQGJs; (3chajO(B-19 ((3eQV(B)s -- (3ebGdGJ heMGVQGJs